0003 Deep-brain Imaging Identifies Cataplexy-on Neurons In The Amygdala. (12th April 2019) - Sun, Ying; Blanco-Centurion, Carlos; Vidal-Ortiz, Aurelio; Luo, Siwei; Zou, Bingyu; Shiromani, priyattam; Liu, Meng
Abstract: Introduction: Amygdala is involved in emotion, and cataplexy is triggered by emotions. We have rescued cataplexy through orexin gene transfer into amygdala neurons (Liu et al., 2017), but seek to further identify culprit neurons triggering cataplexy. We use deep-brain imaging to visualize the activity of the central nucleus of amygdala (CeA) neurons in narcoleptic mice. This method uses a miniature microscope to visualize changes in fluorescence in individual neurons (Ghosh et al., 2011). Methods: GCaMP6s was transduced into CeA GABA neurons in narcoleptic VGAT-Cre mice (VGAT-Cre+/OXKO)(anesthesia) and three weeks later fluorescent activity of individual GABA neurons were extracted with PCA-ICA analysis (Inscopix). Results: 128 neurons were recorded from three narcoleptic mice. Activity of CeA GABA neurons was significantly higher in active waking (AW) and REMS compared to QW or NREM, a profile similar to the vGAT neurons in the lateral hypothalamus. Six GABA neurons (4.7%) were active exclusively in cataplexy. Conclusion: In canine narcolepsy, cataplexy-on neurons in the amygdala have been identified (Gulyani et al., 2002). We have now discovered such neurons in narcoleptic mice. Abnormal activation of these neurons by emotion may trigger cataplexy. Ghosh, K.K., Burns, L.D., Cocker, E.D., Nimmerjahn, A., Ziv, Y., Gamal, A.E. & Schnitzer, M.J. (2011) Miniaturized integration of a fluorescence microscope. Nat Meth, 8, 871-878. Gulyani, S., Wu, M.F., Nienhuis, R., John, J. & Siegel, J.M. (2002) Cataplexy-related neurons in the amygdala of the narcoleptic dog. Neuroscience, 112, 355-365. Liu, M., Blanco-Centurion, C. & Shiromani, P.J. (2017) Rewiring brain circuits to block cataplexy in murine models of narcolepsy. Curr Opin Neurobiol, 44, 110-115 Support (If Any): NIH: NS096151, NS101469; NS052287 (PJS), NS079940 (PJS), NS098541 (PJS), and Veterans Affairs (BX000798, PJS).